Functional impairments in white matter syndrome of neuropsychiatric systemic lupus erythematosus are similar to those observed in patients with multiple sclerosis - Denise Sisterolli-Diniz; Aline de Oliveira; Daiany Silva de Paula; Rosangela Vieira Rodrigues; Nilzio Antônio da Silva (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: In order to compare white matter syndrome of neuropsychiatric systemic lupus erythematosus (NPSLE) and multiple sclerosis (MS), an assessment on demographic, medical history, and clinical data was proposed. METHODS: Sixty-four patients with NPSLE and 178 with MS answered a questionnaire and were evaluated regarding functional system, expanded disability status scale (EDSS), Beck depression inventory (BDI), and Beck anxiety inventory (BAI). RESULTS: The prevalence of autoimmune diseases and altered consciousness was similar in both groups, however it was higher than in the general population. Systemic signs and symptoms occurred from 2.9 to 61.9% of the MS cases, while neurological signs and symptoms occurred in 9.4 to 76.4% of the NPSLE ones. The motor, visual, and mental systems were the most affected in both diseases. The BDI in NPSLE had higher scores and the BAI in MS. CONCLUSIONS: The functional impairments in NPSLE were similar to those of MS, although greater impairment of the functional systems of cerebellar, sensitivity, and sphincters occurred in MS cases, and greater symptoms of depression, anxiety, and headache also occurred in it.